Implementasi Strategi Branding dalam Meningkatkan Pendapatan Pelaku UMKM Nasabah BTPN Syariah di MMS Krembung - Nazwa, Kafilatun; Kurniasari, Irma (Universitas Pahlawan Tuanku Tambusai, 2026)
Micro Small and Medium Enterprises (MSMEs) play a strategic role in increasing the income of local businesses. However, many MSMEs, especially BTPN Syariah customers, have yet to optimize branding-based marketing strategies and consider trademarks to be less important. This assistance program aims to increase MSME income through the implementation of branding strategies, particularly through the creation and strengthening of attractive and informative trademarks. The assistance method is carried out through direct assistance, branding education, and the implementation of business promotion media. The results of the program show an increase in MSME actors' understanding of the importance of branding, the formation of a more professional business identity, and the potential for increased business competitiveness and income.